A Descriptive Tour of the Semantic Structures Apply to Video Surveillance Systems - Cartuche Flores, C. (2015)
Automatic systems that monitor human behavior for detecting security problems are a challenge today. In this work, we analysing the semantic structure required to representing the human behaviour in high-level semantic events. We identify the principal components of different ontologies and describe the goal of each semantic structure. This work describes Horus, because we believe that this framework is a good example of a methodology composed to different levels, the goal is to describe human behavior a video surveillance systems. We propose an idea to complete Horus based in semantic structures. The finish work is obtain an art state about semantic structures apply to video surveillance systems, and generating conclusions and future works from of theory.